VD_FINDINFO HC / 2012 / 49 vom 20. Januar 2012 - VD Tribunal cantonal (2012)
CERTIFICAT D'HÉRITIER, RÉPUDIATIONDROIT SUCCESSORAL, RECTIFICATION DE LA DÉCISION, RECONSIDÉRATION | 570 al. 1 CC, 570 al. 2 CC, 570 CC, 248 CPC (CH), 104 CDPJ, 109 al. 3 CDPJ